Potential Products from Tropical Algae and Seaweeds, especially with Reference to Malaysia - Phang, Siew-Moi (Malaysian Journal of Science, 2010)
Global production and utilization of algae is a multi-billion dollar industry. There is a diversity of tropical algae and seaweeds which have yet to be fully explored for commercial products. Potential products include nutraceuticals, cosmeceuticals, feed, biopharmaceuticals, phycocolloids, horticultural aids and biofuels. Native, indigenious species should be used for industrial applications as introduced species may become invasives and cause environmental and biodiversity problems. Issues to be addressed in the development of an algae/seaweed industry include: species selection, mass-production system (photobioreactor versus open systems), productivity & product yields, harvesting, and downstream processing. To make the commercialization cost-effective, the approach of ’multi-strategies coupled with multi-products’ is essential. Penghasilan dan penggunaan alga merupakan industri yang bernilai berjutaan ringgit/dolar. Pelbagai sumber alga dan rumpair laut tropika masih belum digunakan dengan sepenuhnya sebagai produk komersial. Produk berpotensi termasuklah nutraseutikal, kosmeseutikal, makanan haiwan, biofarmaseutikal, fikokoloid, bahan hortikultur dan biofuel. Spesies-spesies tempatan dan asli harus digunakan untuk aplikasi industri, kerana ada kemungkinan spesies asing akan menjadi invasive dan mengakibatkan masalah-masalah sekitaran dan biodiversiti. Isu-isu yang mesti ditimbangkan dalam perkembangan industri alga/rumpair laut termasuk: pemilihan spesies, sistem pengkulturan secara besar-besaran (foto-bioreaktor lawan system terbuka), produktiviti & hasil, penuaian, serta pemprosesan downstream. Pendekatan ’multi-strategi bersama multi-hasil’ pasti diikuti supaya proses pengkomersilan menjadi kos-efektif.